Chronic eosinophilic pneumonia. - Bento, João (2010)
Idiopathic chronic eosinophilic pneumonia (ICEP) is a rare disorder of unknown cause, associated with intense and abnormal eosinophilic lung infiltration. Most cases occur in patients with prior history of atopy and asthma. It is characterized by subacute or chronic presentation, alveolar and blood eosinophilia and peripheral pulmonary infiltrates on chest imaging, which are sometimes migratory. All treated patients show good and rapid response to systemic corticosteroid therapy and favourable prognosis, however relapses are frequent after weaning or stopping treatment. By this reason, in about one-half of patients long-term systemic corticosteroid therapy is needed. We describe 2 clinical cases of ICEP which diagnosis was established after exclusion of any known cause of eosinophilic lung disease that represents different clinical, laboratorial and radiological patterns of this disease and are discussed in the context of the available data about ICEP and the differential diagnosis with other causes of pulmonary eosinophilia.